41.3 ASSOCIATIONS BETWEEN CHILDHOOD TRAUMA AND PREMORBID ADJUSTMENT, COGNITIVE PERFORMANCE AND BRAIN STRUCTURE AND CONNECTIVITY IN SCHIZOPHRENIA AND HEALTHY CONTROLS. (9th April 2019) - Emsley, Robin; Asmal, Laila; Kilian, Sanja; Plessis, Stéfan Du
Abstract: Background: Childhood trauma (CT) is a recognized risk factor for schizophrenia and it has been proposed that CT interferes with normal neurodevelopment, possibly as an adaptive process that persists, thereby establishing a biological vulnerability in the pre-schizophrenic individual. Childhood abuse and neglect may have differential effects on the brain, and different pathways to psychosis, with abuse affecting stress-sensitive brain regions and being associated with prominent affective symptoms, and neglect being associated with generalized brain structural changes, prominent cognitive impairments and a poorer outcome. Methods: We conducted a series of studies to investigate relationships between CT and three proxies of neurodevelopment, namely 1) premorbid adjustment, 2) cognitive performance and 3) brain structure and white matter connectivity, in minimally treated patients with a first-episode of schizophrenia or schizophreniform disorder (n = 56) and community matched healthy controls (n = 52). Results: Patients and controls reported high levels of CT. A history of CT was associated with poorer social and academic premorbid adjustment. Obstetric complications, substance abuse and poor motor coordination weakened some of the associations while poor sequencing of motor acts strengthened the association. Cognitive performance was poorer for patients compared with controls. Childhood neglect significantly predicted impairment in social cognition in both patients and controls. Neglect also significantly predicted poorer verbal learning in patients and attention/vigilance in controls. Childhood abuse did not significantly predict cognitive impairments in either patients or controls. Regarding white matter connectivity, patients who experienced high levels of CT had significantly lower fractional anisotropy (FA) in several cortico-limbic circuits compared with controls who experienced high levels of childhood trauma. Patients with a history of childhood sexual abuse had lower FA in compared with patients without a history of sexual abuse. Patients who had experienced childhood emotional neglect had higher FA in the right superior longitudinal fasciculus compared to patients with low levels of emotional neglect. Finally, we examined the effects of CT on hippocampal subfield morphometry using FreeSurfer 6.0 software. We found a significant interaction between sex*CT*diagnosis across hippocampal sub-regions, with subiculum volumes positively correlating with the CT score in male patients. Conclusions: These findings suggest trauma-specific effects of CT on social and academic premorbid adjustment, social cognition and white matter connectivity. There is a complex interplay of various risk factors, supporting the notion of different pathways to psychosis. The relationship of CT with subiculum volume is of particular interest given the key role of this structure in dopamine release and the proposal that its disruption is the common pathophysiological basis for both schizophrenia and stress.